Systematic approach of using power save mode for cloud data processing services. (31st July 2012) - Kim, Hyeong S.; Shin, Dong In; Yu, Young Jin; Eom, Hyeonsang; Yeom, Heon Y.
Energy efficiency is becoming a key issue for IT operators and data centres. To provide Power Save Mode (PSM) for data processing applications in such environments, power down method as a scaling down technique is an effective solution toward energy proportionality. The existing solutions for the PSM are inefficient in the overall energy management, taking the full replication approach. We propose an efficient replica redistribution algorithm, and our experimental results show that our system significantly reduces the network usage and the elapsed time. Our system leads to a slight increase in running time compared with the full replication approach.